Dichos de vida y muerte en "Campo general" de João Guimarães Rosa - Alves, Maria Theresa Abelha (Verbum – Analecta Neolatina, 2012)
This article, while discussing the relationship between language and death, shows the origin and consequences of the tragedy unfolding in the novel by Guimarães Rosa - Campo Geral - through the eyes of two little brothers - Miguilim and Dito - who lose their innocence by discovering the family secrets involving betrayal of fraternal and marital law. The death creeps into narrative through symbolic and real deaths that occur as acts in language and speech.